Significance of corporal practices in the treatment of the chemical dependency - Giuliano Gomes de Assis Pimentel; Edna Regina Netto de Oliveira; Aparecida Paulina Pastor; Philip Sidney Pacheco Badiz (Faculdade de Medicina de Botucatu (Unesp), 2008)
The aim of this study was to analyze the social representations of addicted or chemically dependent women and the contribution of physical exercises and body activities to their recovery process and reinsertion into society. Fourteen women hospitalized in a rehabilitation institution were interviewed and observed in relation to their participation in a physical fitness program (corporal practice), systematized in the form of games and physical exercises. Their reports and practices revealed contradictions between their sensations, reasons or justifications, and perspectives related to the use of their own body. Based on the results, an attempt was made to understand how the social life conditions mediate the way such women organize themselves in benefit of their own health.